Balancing Principles of Legality in Teaching Legal Studies - Ali Masyhar (The Indonesian Journal of International Clinical Legal Education, 2019)
The principle of legality is a fundamental doctrine in criminal law. At the time of its emergence, it served as an oasis amid widespread uncertainty, when the law was considered the property of the king. Individuals had no means of knowing whether their actions were lawful, as everything depended on the monarch’s subjective judgment. With the adoption of the legality principle, this absolute power was removed. The authority to determine guilt was transferred to the judiciary, and even judges were constrained to apply legal provisions strictly, without expansion or reduction. Whether an act constituted a crime became a matter defined explicitly by written law. Consequently, no conduct could be punished if it was not formally stipulated as a criminal offense. However, this principle also has significant limitations. Acts that are socially harmful but not codified—such as those rooted in customary norms—cannot be subjected to criminal sanctions. This represents a major weakness of the legality principle. When applied rigidly, another drawback may arise: individuals may be easily criminalized for merely fulfilling the elements of a written offense, even when, in sociological terms, their actions do not cause actual harm or legal injury, either materially or immaterially.